Opening Day (Seville Enterprises, Inc.)
Opening Day Celebration. President Richard M. Nixon officially opening Expo '74 on the specially built floating center stage surrounded by floats of nations. With him on stage is Mrs. Nixon and Governor Daniel J. Evans.